PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI OCB - Angga Kifari Zakawali; Sri Nawatmi (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
The purpose of this research is to observe the employees of PT. Nasmoco Siliwangi Semarang which totals 94 people in the population. The Non Probability Sampling method is used where all members of the population are taken as a sample. In this study, 94 employees of PT. Nasmoco Siliwangi Semarang with various positions were taken as samples. The data used are primary data obtained through questionnaires. The variables studied include the influence of leadership style and organizational culture on employee performance, with OCB (Organizational Citizenship Behavior) as the mediating variable. Data analysis was performed using multiple linear regression methods with the help of SPSS 29 software.